Acidic characteristics of fermented and dried cocoa beans from different countries of origin - Jinap, Selamat; Dimick, Paul S. (Wiley, 1990)
Thirty-nine fermented and dried cocoa bean samples from 13 countries were evaluated for pH, titratable acidity and concentrations of volatile and nonvolatile acids. The correlation coefficient between pH and log10 titratable acidity was -0.94. Cocoa beans from Brazil and Far Eastern countries were highly acidic while those from Central American and South American countries were low in acidity. Samples from West African countries were intermediate with titratable acidity values from 0.12 to 0.15 meq NaOH/g sample and pH values from 5.20 to 5.49. Highly acidic beans were characterized by high concentrations of acetic and lactic acids. The high correlation between acetic acid and both pH (r=0.86) and titratable acidity (r = 0.91) indicated that this acid could be primarily responsible for high acidity in cocoa beans.